Fuzzy-like multiple objective decision making - Xu, Jiuping (Studies in fuzziness and soft computing, 2011)
Using real-life problems, this book presents applications of the fuzzy-like multi-objective decision making (FLMODM) model. It proposes the basic theories, models and algorithms and applies them to solve realistic problems